Unveiling the glass ceiling phenomenon and mitigating strategies through organizational justice: a conceptual paper - Keiko Sweetie Watanabe; Abdul Hamid Kwarteng (Cogent Business & Management, 2024)
The article proposes a conceptual framework to explain how organizational justice can mitigate the negative effects of glass ceiling on women's career advancement and consequently create an equal ground for women to advance their careers just like their male counterparts. The article uses the Social Role theory and the Rawlsian theory of justice to propose a conceptual model with hypotheses that are backed by logical and theoretical arguments. This conceptual paper proposes that personal, societal, and organizational barriers would have a negative effect on women's career advancement but organizational justice could positively moderate such a relationship by eliminating the negative effects of glass ceiling and thereby creating equal competitive grounds for both women and men to advance in their career. The paper offers practical suggestions on the need for managers to give the needed attention and importance to the three main dimensions of organizational justice as this has the possibility of ensuring that glass ceiling is reduced to the barest minimum in order to create a conducive environment will be created for both men and women to progress in their career. Thus the paper argues that organizational justice can moderate the negative relationship between glass ceiling and women's career advancement.
Keywords: 650; Organizational justice; glass ceiling; personal barriers; societal barriers; organizational barriers; women's career advancement; equal opportunities